UMP sustainable campus greenery initiatives as new attraction - Nor Salwana, Mohammad Idris (2021)
PEKAN, 2 March 2021 - Universiti Malaysia Pahang (UMP) launches campus greenery project involving tree planting zones, forest zones and open areas to be planted with natural plants.